أثر الخصخصة على المال العام في سلطنة عمان - Muntasar Ibn Salam Ibn Salih Al-Harrasi (2024)
E-PROCEEDING 3rd INTERNATIONAL CONFERENCE OF THE POSTGRADUATE STUDENTS AND ACADEMICS IN SYARIAH AND LAW 2020 (3rd INPAC 2020) "Syariah and Law Approach in Solving Contemporary Issues" Organized by: Faculty of Syariah and Law Date: 18 November 2020